1993
DOI: 10.1111/j.1471-0528.1993.tb15112.x
|View full text |Cite
|
Sign up to set email alerts
|

What is vestibular papillomatosis? A study of its prevalence, aetiology and natural history

Abstract: Objectives To clarify the prevalence, aetiology, symptoms and natural history of vestibular papillomatosis. Design Study in two parts: 1. prevalence assessed by colposcopic examination of the vulva of unselected patients by one doctor (J.M.W.); 2. patients selected by clinical appearance as having vestibular papillomatosis (by J.M.W. and other doctors) assessed in a research clinic. Setting Outpatient genitourinary medicine clinic in South London. Subjects Part 1 study: 295 female clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 11 publications
2
27
0
2
Order By: Relevance
“…VP histopatolojisi, normal vulvar epitelle kaplı fibrovasküler dokunun parmaksı uzantıları ile karakterizedir. Bazen viral infeksiyonlarda görülen koilositoza benzer vakuolize epitel hücreleri görülebilir, ancak, bunların vestibüldeki epitel hücrelerinin içeriğinde oldukça fazla olan glikojene ve doku proçesi sırasında vakuolize olmalarına bağlı olduğu düşünülmektedir 1,3 . Görünüm olarak genital verrülere benzeyebilen papüller, verrülerden farklı olarak tek tek yerleşirler ve yüzeyleri daha düzdür, verrüler ise daha sert olup tabanlarından birleşme eğilimindedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…VP histopatolojisi, normal vulvar epitelle kaplı fibrovasküler dokunun parmaksı uzantıları ile karakterizedir. Bazen viral infeksiyonlarda görülen koilositoza benzer vakuolize epitel hücreleri görülebilir, ancak, bunların vestibüldeki epitel hücrelerinin içeriğinde oldukça fazla olan glikojene ve doku proçesi sırasında vakuolize olmalarına bağlı olduğu düşünülmektedir 1,3 . Görünüm olarak genital verrülere benzeyebilen papüller, verrülerden farklı olarak tek tek yerleşirler ve yüzeyleri daha düzdür, verrüler ise daha sert olup tabanlarından birleşme eğilimindedir.…”
Section: Discussionunclassified
“…VP vulvanın anatomik bir varyantı olarak değerlendirilmekte ve erkeklerde görülen incimsi (pearly) penil papüllerin kadınlardaki eşdeğeri olarak düşünülmektedir 1,2 . Prevelansı %1 olarak bildirilmiştir 3 . Ülkemizde VP görülme sıklığı ile ilgili bir çalışma bulunmamaktadır ve yurt içi literatürde konu ile ilgili yayınlar bir olgu bildirimi ile sınırlıdır 4 .…”
Section: Gi Riflunclassified
“…1 It is characterized by linear, pink, smooth or filiform papules symmetrically distributed on the inner surface of both labia minora.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VP was estimated to be 1 % of the women examined consecutively in an outpatient gynaeco logical practice [2], However, in a population-based study of 611 young women, it was found that 35% had some degree of papillomatous structure of the inner aspects of the labia minora [3]. Attention needs to be paid to this condition, as many women complaining of itching, burn ing, and dyspareunia are found to have VP [4].…”
mentioning
confidence: 99%
“…Attention needs to be paid to this condition, as many women complaining of itching, burn ing, and dyspareunia are found to have VP [4]. Pro nounced VP is observed in many women who have or have had condyloma acuminatum or cervical intra-epi- thelial neoplasia (CIN), giving reason to supsect human papillomavirus (HPV) as an aetiological factor [2], How ever, VP may be totally asymptomatic, and there is a widespread belief that the condition represents a normal but unusual physiological variant of epithelial folding [5,6]. The aim of this study was to determine whether HPV is present in prominent vestibular papillae or filaments seen in women with other signs of HPV infection and in those with severe vulvar itching or pain.…”
mentioning
confidence: 99%